Development Strategy for Wellness Hotels in Ukraine - Parfinenko Tetiana O.; Rzaeva Tamila H. (Bìznes Inform, 2025)
The Russian invasion of Ukraine has significantly affected the development of the entire hotel industry, in particular the functioning of Wellness hotels. In the first year of the full-scale invasion, there was a significant decline in the number of tourists and holidaymakers, but since 2023, hotel occupancy rates have started to increase. Such transformations are driven by the need for Ukrainians to recover from moral and psychological turmoil and the growing number of people with various types of injuries and disabilities. Significant changes are also observed in the concept of resort regions, age group, consumer needs, management style, competitive environment, investment climate, etc. This situation requires the search for new strategies for the development of Wellness hotels, which will lead to entering new markets, increase competitiveness, stabilise money flows and increase the capitalisation of the enterprise. The aim of the study is to provide a scientific substantiation of the methodological foundations for the formation of a strategy for the development of Wellness hotels. The study has used general scientific and economic research methods, in particular, the method of comparative analysis, using which the discrepancies between the general trends in the development of Wellness hotels worldwide and the situation in Ukraine were determined; statistical method was used to determine the current state of the Wellness hotel market and to compare it with the pre-war period; the expert assessment method was employed to forecast the development prospects of Wellness hotels in Ukraine; to study the internal and external environment of Wellness hotels and to formulate a strategic plan for enterprises, the method of strategic analysis was used. The article reveals the theoretical and methodological foundations of forming a strategy for the development of Wellness hotels. Based on the analysis, a strategic plan for the development of Wellness hotels has been proposed. Effectiveness of development strategies, based on a hierarchical analysis of indicators of strategic potential, has been assessed and its graphical representation has been provided. In order to make strategic management decisions, a matrix of "McKinsey-General Electric" has been built. On the basis of the analysis, a strategy for diversification of activities has been proposed, which provides for the enterprise's entry into new business areas. On the basis of strategic analysis, the research allows to determine the mission, goals and objectives of Wellness hotels, to develop the main directions of their development to ensure a balanced operation of the enterprise in the context of dynamic changes in the external environment and maximum use of all its resources.